The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1989
DOI: 10.1002/ijc.2910440604
|View full text |Cite
|
Sign up to set email alerts
|

The subcellular localization of the neu protein in human normal and neoplastic cells

Abstract: We have examined the subcellular localization of the neu protein by immunohistochemistry and immuno-electron microscopy, associated with immunoblotting of normal and neoplastic tissues with 2 monoclonal antibodies (MAbs). Immunoelectron microscopy clearly reveals that neu protein resides only on the lateral plasma membrane of the simple epithelium of the breast and on the plasma membrane of malignant breast cells. It is also found on the membranes of the microvilli and the apical vacuoles of the cells of the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
43
0

Year Published

1991
1991
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(47 citation statements)
references
References 20 publications
4
43
0
Order By: Relevance
“…From this study we conclude that c-erbB-2 membranestaining tumours spread, especially to the liver, which confirms a previous prospective study with a short follow-up period (De Potter et al, 1989b). The particular pattern of metastasis to the liver could be explained with the production of a factor in the liver which stimulates the growth and spread of c-erbB-2 tumour cells.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…From this study we conclude that c-erbB-2 membranestaining tumours spread, especially to the liver, which confirms a previous prospective study with a short follow-up period (De Potter et al, 1989b). The particular pattern of metastasis to the liver could be explained with the production of a factor in the liver which stimulates the growth and spread of c-erbB-2 tumour cells.…”
Section: Discussionsupporting
confidence: 89%
“…Membrane staining with antibodies against the cerbB-2 protein is known to be related to DNA amplification (Venter et al, 1987;Gusterson et al, 1988;Walker et al, 1989) and is considered to be the only expression of the c-erbB-2 oncogene, as cytoplasmic staining was shown not to be related to c-erbB-2 expression (De Potter et al, 1989b).…”
Section: Discussionmentioning
confidence: 99%
“…The cytoplasmic staining of p185 c-erbB-2 has already been reported in prostate cancers (Rosset et al, 1993). De Potter et al (1989) have described the presence of a protein on the mitochondrial membrane, appearing as granular staining in the cytoplasm. The significance of the cytoplasmic staining in breast cancer cells is controversial, since some authors did not observe a correlation between the cytoplasmic protein and the mRNA levels (DiGiovanna, 1999;Ross and Fletcher, 1999 have analysed, there was a good correlation between these parameters.…”
Section: Discussionmentioning
confidence: 99%
“…De Potter et al (1989) have suggested that these may represent the c-erbB-2 cell membrane protein and a 155 kD protein associated with the mitochondrial membrane. The smaller of these may represent a partially glycosylated form of the protein since inhibition of N-linked glycosylation by tunicamycin has been shown to produce an immunoprecipitable protein of 155-160kD in human cells which express c-erbB-2 .…”
Section: Discussionmentioning
confidence: 99%